Realizing the Development Potential of Filipino Diaspora Philanthropy - Añonuevo, Augustus T.; Añonuevo, Estrella Mai Dizon (Philippine Journal of Social Development, 2011)
Financial, material, and other contributions and donations of overseas Filipinos are largely sent to their communities of origin in the Philippines.   Such philanthropy of the Filipino diaspora remains predominantly characterized by charitable giving focused on providing immediate assistance to those most in need in the Philippines.   There are, however, emerging practices of strategic philanthropy of overseas Filipinos. The Asia Pacific Philanthropy Consortium (2007) defines strategic philanthropy by diaspora populations as “investments that fund longer term and sustainable solutions and social change in home countries, as opposed to charitable giving that addresses immediate needs, and beyond remittance transfers that fulfill familial obligations”. The study cited several examples of Filipino diaspora organizations — in partnership with NGOs, foundations, and/or local and national government agencies — engaged in strategic philanthropic investment aimed at sustainable development and social change. The cases of Ayala Foundation-United States of America, Answer for the Cry of the Poor/Gawad Kalinga and their partner overseas Filipino organizations and individuals were discussed and analyzed as exemplary efforts of strategic diaspora giving/philanthropy. The paper also cited the challenges that must be addressed and put forward recommendations for Filipino diaspora philanthropy to achieve significant scale and scope, and create meaningful impact on Philippine development.